1992
DOI: 10.1016/0378-1097(92)90439-u
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and energetics of antiseptic and disinfectant resistance in Staphylococcus aureus

Abstract: Clinical isolates of Staphylococcus aureus carry various antiseptic and disinfectant resistance determinants (qac genes) on a variety of plasmids. The biochemistry and specificity of these resistance genes in S. aureus is the subject of this report. The qac genes were separated into two families on the basis of resistance profiles and DNA homology. Isotopic and fluorimetric assays demonstrated that the qac genes encode efflux systems that rely on proton motive force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
149
0
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(162 citation statements)
references
References 33 publications
9
149
0
4
Order By: Relevance
“…On the other hand, it has also been shown that the over production of proteins functioning as efflux pumps makes cells highly resistant to a variety of antimicrobial agents (Littlejohn et al 1992;Lomovskaya and Lewis 1992;Edgar and Bibi 1997;Mine et al 1999;Jack et al 2000). Several types of efflux pumps exist, mostly consisting of a set of protein elements, and they exclude various agents with no homologous structures, out of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has also been shown that the over production of proteins functioning as efflux pumps makes cells highly resistant to a variety of antimicrobial agents (Littlejohn et al 1992;Lomovskaya and Lewis 1992;Edgar and Bibi 1997;Mine et al 1999;Jack et al 2000). Several types of efflux pumps exist, mostly consisting of a set of protein elements, and they exclude various agents with no homologous structures, out of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa, and have suggested that the increases in quantities of cellular membrane components, such as phospholipids, fatty acids and neutral lipids, suppress the adsorption of benzalkonium chloride molecules to the cell. Apart from such an alteration in the cell envelope, the active efflux of cationic surfactant, as an alternative mode of the acquired resistance, has also been shown in staphylococci (Littlejohn et al 1992;Heir et al 1995Heir et al , 1998. These two distinct modes of acquired resistance have often been described for antibiotics and, in particular, the increased development of an efflux system brings about multi-drug resistance (Nikaido 1994).…”
Section: Introductionmentioning
confidence: 99%
“…PMF-dependent multidrug efflux proteins have been classified into three distinct families of membrane transport proteins based on comparative sequence analysis: the major facilitator superfamily (4 -6), e.g. Bmr from Bacillus subtilis (7) and QacA from Staphylococcus aureus (8,9); the small multidrug resistance family (10), e.g. EmrE from Escherichia coli (11) and Smr from S. aureus (12,13); and the resistance/nodulation/cell division family (14), e.g.…”
mentioning
confidence: 99%
“…The multidrug resistance gene qacA is encoded on multiresistance plasmids from clinical isolates of S. aureus and confers resistance to a wide range of antimicrobial organic cations, including various dyes, Qacs, diamidines, biguanidines, and guanylhydrazones (8,9,17). qacA encodes a membrane protein, QacA, with 14 TMS (18) providing resistance to ethidium via a PMF-dependent export mechanism (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation